ANALISIS JARINGAN KOMUNIKASI ORGANISASI KONFEDERASI SERIKAT BURUH INDONESIA DALAM MENOLAK UNDANG-UNDANG NOMOR 6 TAHUN 2023 TENTANG CIPTA KERJA - Shahreza, Mirza; Erik Setiawan (Jurnal Studi Komunikasi dan Media, 2024)
This research aims to describe who the dominant/central actors are and what the relationships between actors in the KSBSI organizational network are regarding the rejection of Law Number 6 of 2023 concerning Job Creation. This research method uses a communication network analysis method with a descriptive type, data analysis techniques using Eriyanto's theory, (2014) consisting of structured data analysis, unstructured analysis and observation. The results of this research show that the actor with the name Harris Manalu became the dominant/central actor when rejecting Law no. 6 of 2023 concerning job creation, by occupying the four best centrality positions including: level centrality (8), closeness centrality ( 8), centrality of betweenness (8.167) and eigenvector (0.459). Meanwhile, relations between actors in the KSBSI organizational network mostly use relationship types: interests (4), hierarchical or authority/power (3), emotional (2) and communication (1). In this study, researchers did not find any type of transaction or kinship relationship, based on information that the actors who were part of the KSBSI legal team in rejecting the law did not have any transactions and the actors came from different backgrounds.